2016
DOI: 10.4236/ojra.2016.63013
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Serum Uric Acid with Disease Activity and C-Reactive Protein in Patients Suffering from Rheumatoid Arthritis

Abstract: Rheumatoid Arthritis is characterized by increased cardiovascular morbidity and mortality that cannot be fully explained by the presence of classical cardiovascular disease (CVD) risk factors suggesting that novel risk factors may play a role. Evidence accumulated over the past decade points that uric acid (UA) may be one such novel CVD risk factor in rheumatoid arthritis, and therefore one may hypothesize that UA may contribute to the increased CVD burden in RA. The current study attempted to correlate the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This could be explained by the long disease duration and that our patients were already on DMARDs which control the disease activity and at the same time has great effect on level of serum uric acid. Alternatively, Ghosh et al (13) found a positive correlation between serum UA and clinical disease activity index and hs-CRP with extremely high statistical significance in 120 newly diagnosed DMARD naive RA patients of them 36 patients were males.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the long disease duration and that our patients were already on DMARDs which control the disease activity and at the same time has great effect on level of serum uric acid. Alternatively, Ghosh et al (13) found a positive correlation between serum UA and clinical disease activity index and hs-CRP with extremely high statistical significance in 120 newly diagnosed DMARD naive RA patients of them 36 patients were males.…”
Section: Discussionmentioning
confidence: 99%
“…The rheumatoid factor (RF) monitors the presence of an antibody in most patients with RA [ 90 ]. Interestingly, for inflammatory arthritis, uric acid and CRP increase in gout [ 91 ]. On the other hand, biomarkers may allow for the diagnosis of inflammatory arthritis at early stages of the disease.…”
Section: Nanomaterials For the Diagnosis Of Inflammatory Arthritismentioning
confidence: 99%